Role of Innovation and Entrepreneurship Education in Enhancing Graduate Employability in Vocational Higher Education: A Systematic Literature Review - Xiong Yijun; Sururi Sururi; Taufani Chusnul Kurniatun (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2026)
Abstract: This study aims to examine the role of innovation and entrepreneurship education in enhancing graduate employability in vocational higher education through a Systematic Literature Review (SLR) and bibliometric analysis. In the context of rapid technological change and increasing labor market demands, vocational higher education institutions are expected to produce graduates who are not only technically competent but also innovative, entrepreneurial, and adaptable. This study analyzed 41 Scopus-indexed publications published between 2021 and 2026, with data processed using VOSviewer to identify research trends, keyword relationships, thematic clusters, and the knowledge structure of the field. The findings reveal that employability is the dominant and central theme, strongly associated with innovation, entrepreneurship education, digital skills, soft skills, and work-based learning. The keyword co- occurrence analysis indicates a shift from a traditional skills-based orientation toward a more integrated and multidimensional understanding of employability, emphasizing not only technical competencies but also creativity, communication, collaboration, adaptability, and lifelong learning capacity. In addition, the distribution of authors, institutions, and countries demonstrates that this topic has attracted global scholarly attention, particularly in developing and transitional economies, although the field remains fragmented and continuously evolving. The study concludes that enhancing graduate employability requires a holistic ecosystem that integrates curriculum innovation, entrepreneurial learning, digital capability development, and strong collaboration between educational institutions and industry. It is recommended that future research develop integrative frameworks and explore context-specific strategies to strengthen the alignment between vocational education and labor market needs. Keywords: employability, entrepreneurship education, innovation education, vocational higher education.